Glasrutor i en skogsgård - Andersson, Josefina; Welinder, Stig (Hikuin, 2010)
Window panes at a forest farm By Josefina Andersson and Stig Welinder Grannäs is a Forest Finn farm from the 17th century in the province of Hälsingland in Midsweden. It can be considered peripheral both in a local context, being in marginal woodlands, and in a broad North European perspective. The Forest Finns migrated from Finland to the Scandinavian Peninsula in the beginning of the 17th century. There are abundant pieces of broken window panes in and around the farm house with a traditional Finnish smoke oven. There was a window with several panes and leaden window bars in the southern timber wall of the house. The panes were smashed several times during the century of use of the house. Some of the pieces of glass have melted, as has some lead from the bars, when the house burned, which happened at least twice. The small pieces of glass were still situated by the window at the time of the archaeological excavation. Big pieces had been thrown behind the house or between the smoke oven and the timber wall of the house. The pieces that had been scattered in the farm yard had been crushed into small shards by feet, hooves and wheels. Among the pieces, at least half a score of different panes can be recognized from the thickness and colour of the glass. Broken window panes were replaced several times. The forest farm Grannäs, despite its peripheral location, had obviously been part of a market economy in which glass window panes were produced, distributed and used. In 17th century excavations all over Scandinavia pieces of glass panes are extremely common. The exceptions are a few country-side farms like the Forest Finn farm Gammelvallen in the province of Värmland and the tenancy farm Vall in the province of Gästrikland.